Characteristics of A/B-type starch-wheat germ oil complexes and their effects on noodle texture. (June 2021) - Yan, Huili; Lu, Qiyu; Gui, Jun
Abstract: The characteristics of A-starch-wheat germ oil complex (A-SWGOC) and B-starch-wheat germ oil complex (B-SWGOC) and their effects on noodle texture were investigated. A-starch exhibited a higher reactivity toward encapsulating wheat germ oil (WGO). Although A-SWGOC and B-SWGOC had similar crystallinities and short-range ordered structures, A-SWGOC showed a higher swelling power (12.11) and decomposition temperature (308.39 °C). One additional peak appeared in the pasting profile of A-SWGOC, probably due to the dissociation and reassociation of amylose-lipid complexes, while this phenomenon did not occur for B-SWGOC, suggesting a different structural basis for amylose-lipids in A-SWGOC and B-SWGOC. The amylose-lipid complexes had no obvious influence on the digestibility of starches, but the inherent attributes of A- and B-type starch rendered A-SWGOC more resistant starch (RS, 53.51 g/100 g starch) but B-SWGOC more slowly digestible starch (SDS, 42.38 g/100 g starch). Compared with their respective controls, the existence of A-SWGOC can additionally increase the hardness of noodles tested at 2 h and the chewiness, cohesiveness and resilience at 0 h and 2 h, respectively, while B-SWGOC can only increase the hardness and chewiness; in general, A-SWGOC was more conducive to increase the hardness and maintain the chewiness and springiness of noodles during storage. Highlights: Two peaks emerged in the RVA profile of A-starch-wheat germ oil complex (A-SWGOC). A-SWGOC increased noodle hardness at 2 h to a larger extent. A-SWGOC kept the chewiness and springiness of noodles effectively during storage.